The Role of CSR Engagement in Customer-Company Identification and Behavioral Intention During the COVID-19 Pandemic - Wu, Yanqin; Zhu, Wenzhong (Frontiers in Psychology, 2021)
The global coronavirus pandemic has reignited a strategic debate among the business community of the necessity for corporate social responsibility (CSR) engagement in the ever-dynamic social media. Considering the global economic downturn introduced by the COVID-19 pandemic, the present research is devoted to investigating whether CSR engagement in social media can help DiDi (a Chinese shared brand) at stake survive this overwhelming crisis. A theoretical model proposed to describe the hypothesized relationships was tested by a Structural Equation Modeling technique through the empirical online questionnaire. Through findings, we demonstrated that there was a positive relationship between CSR engagement of DiDi on WeChat, customer–company identification (C–C identification), and behavioral intention [purchase intention, brand loyalty, and e-word-of-mouth (eWOM)] of customers. With attention to psychological influence, our empirical statistics also evidenced the mediating role of C-C identification between CSR engagement and behavioral intention of customers. This study highlights the significant role of CSR engagement in a critical period theoretically and offers businesses more open innovation strategies to compete against the COVID-19 pandemic-induced market downturn.